Phase composition and properties of Fe₂O₃-Al₂O₃ catalytic system in the high-temperature ammonia oxidation process - Zakharchenko, N.I. (Functional Materials, 2005)
The Fe₂O₃-AI₂O₃ catalytic system in the high-temperature ammonia oxidation reaction has been studied. The system phase composition has been shown to influence the physicochemical properties and performance of the catalysts. The catalytic properties of the iron-aluminum system (93.3 mass % by Fe₂O₃ and 6.7 mass % by Al₂O₃) in ammonia oxidation have been determined. The causes of high-temperature catalyst deactivation have been discussed.